PENGELOLAAN HAYATI TANAH UNTUK MENINGKATKAN PERAN FAUNA TANAH SELAMA SATU MUSIM TANAM KEDELAI ORGANIK - CHICHI JOSEPHINE MANALU JOSEPHINE MANALU (JURNAL ILMIAH KOHESI, 2018)
Soil fauna is an organism which undergoes all or most of its life cycles both in the soil body or the soil surface. Organic matter management is aimed at obtaining/providing energy and nutrient resources for soil fauna, so that the diversity of soil fauna is maintained and can play its role in helping to increase plant growth and yield. Each type of soil fauna requires different organic compounds with other fauna species, so it needs plant diversity as an organic source.